Tinjauan Kualitas Genteg Beton Sebagai Penutup Atap Dengan Bahan Tambah Serat Tebu - Pamungkas, Aan; , Ir. Suhendro Trinugroho, MT; , Agus Susanto ST, MT (2015)
Background this research is the quality of the tile concrete with the added fibers cane.The purpose of this study is to find the influence of the addition of fibers cane against: ( 1 ) larger the burden on pliable, ( 2 ) seepage tile concrete, ( 3 ) the absorption of water, ( 4 ) of the nature of looked tile concrete, ( 5 ) uniformity size tile concrete, ( 6 ) the absorption of heat on tile concrete and quality of tile concrete with the added fibers cane and tile concrete without its added.Analysis of the data been conducted from testing is compared in sni and pubi.The result of this research use of added fibers of the sugar cane by comparison 1 cement: 2 lime mill: 2.5 sand while for the addition of fibers cane different namely the percentage of 0 %; 1 %; 1.5 %; 2 %; 2.5 % of heavy sand used.The results of testing burden pliable averages for each the percentage the addition of and cane 0 % = 103,23 kg; 1 percent = 126,49 kg; 1.5 % = 123,57 kg; 2 % = 106,70 kg; 2.5 = 96,22 kg.The results of testing seepage tile concrete by the addition of fibers cane 0 %; 1 %; 1.5 %; 2 %; 2.5 % they did not happened seepage .The results of testing absorption water the average tile concrete to adding fibers cane 0 % = 6,05 %; 1 percent = 7,53 %; 1.5 % = 8,19 %; 2 % = 9,07 %; 2.5 % = 9,44 % .The results of the nature of looked tile concrete to adding fibers cane 0 %; 1 %; 1.5 % there is no crack , a cavity and defect other while in penambahanan fibers cane 2 % and 2.5 % terdapa crack and cavity .The results of testing size tile concrete p = 420 mm , l = 12.5 mm , thick part flattened = 14.1 mm , thick laying on = 8.5 mm , wide laying on = 78 mm , into a groove = 34,5 mm , long passengers = 420 mm. the results of testing absorption of heat the average to adding fibers cane 0 % = 92,47 %; 1 percent = 95,40 %; 1.5 % = 93,00 %; 2 % = 92,37 %; 2.5 % = 94,00 % .